Achieving structural rejuvenation in metallic glass by modulating β relaxation intensity via easy-to-operate mechanical cycling. (October 2022) - Zhang, L.T.; Wang, Y.J.; Pineda, E.; Yang, Y.; Qiao, J.C.
Highlights: An easy-to-operate mechanical cycling as an alternative strategy to tailor the mechanical relaxation, deformation, and structural heterogeneity of metallic glasses was proposed. A theoretical model is constructed which reveals a scenario of that mechanical cycling wakes up frozen flow defect, accelerating creep and enhancing the β relaxation in metallic glasses. It provides comprehensive understanding of the structure-property relationship in metallic glasses, especially with regards to the competition between structural relaxation and rejuvenation. Abstract: Structural rejuvenation is an effective measure to optimize the mechanical properties of metallic glasses (MGs). Sophisticated solutions to rejuvenation include thermal cycling, laser shocking, and multiaxial stress loading. Here, we propose an easy-to-operate mechanical cycling as an alternative strategy to tailor the mechanical relaxation, deformation, and structural heterogeneity of MGs. Structural rejuvenation in a La-based MG is achieved via mechanical cycling even at very few cycles (10 2 tension load cycles) and low frequencies (10 −3 Hz). The results manifest intuitively the competition between structural relaxation and rejuvenation, which constitutes the structural evolution in MGs. A theoretical model is constructed which reveals a scenario that mechanical cycling wakes up frozen flow defect, accelerating creep and, thus, enhancing the β relaxation in MGs. Therefore, this handy anti-ageing methodology provides an alternative pathway to optimize the mechanical properties of MGs. It also contributes to a more comprehensive understanding of the structure-property relationship in amorphous materials, especially with regard to the correlation between structural rejuvenation and relaxation behavior in such topologically disordered materials. Graphical abstract: Image, graphical abstract